Tamanho e densidade das populações de Alouatta guariba clamitans cabrera, 1940 (primates, atelidae) no campo de instrução de Santa Maria e áreas vizinhas - Veiga, Joana Beschorner da (2013)
This dissertation evaluated the age-sex structure, group size and population density of Alouatta guariba clamitans in 40 forest fragments. We also present a Population Viability Analysis for the subspecies. The study was conducted at Campo de Instrução de Santa Maria (CISM), an area of 5,876 ha belonging to the Ministry of Defense (Brazilian Army) and surrounding areas, located in the municipality of Santa Maria (Rio Grande do Sul State, South Brazil). The fieldwork was conducted from March 2012 to February 2013, totaling 58 days and sampling effort of 431 hours. Our data suggest high mortality in the brown howler monkey populations at CISM. The record of low densities, low occupancy rates in fragments and small group size supports our conclusions. Statistical analyzes showed significant differences between the current population parameters and the previously registered. The PVA results suggest the fragment size and adult female survival as the best parameters contributing for the population growth. Yellow fever is an important threat, especially if the incidence of new outbreaks is high. For the long-term persistence of A. g. clamitans at CISM, the minimum viable population must be at least 573 individuals living in a minimum suitable forest area of 516 ha, which is perfectly plausible for the CISM area. In Rio Grande do Sul state there are practically no conservation units, especially in the western range of the distribution of the brown howler monkey and reinforces the important role of CISM in this scenario, although not a conservation unit. Therefore, if the metapopulation dynamics is granted, it is able to ensure regional long-term survival of A. g. clamitans, unless it suffers more intensely other impacts (such as a new yellow fever outbreak) in a near future.